Analisis Aplikasi Mobile Transportasi Online Menggunakan User Experience Questionnaire pada Era Milenial dan Z - Abdillah, Leon Andretti (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
Online transportation becomes so popular in the ride-sharing industry. Young millennial and z generation users utilize their smartphone not only for communications but also for ordering online transportation services like Gojek. This study examines the experience of millennial and z generation students in using the well-known Gojek online transportation mobile service. A number of 154 millennial computer science students as respondents are involved in this study. Their experience in using online mobile transportation services via smartphone was collected through an online questionnaire made using google forms and distributed via Facebook. The tool used in this study is Online User Experience Questionnaire (UEQ). The results showed that all UEQ categories scored in positive areas. The highest score is in the "Perspicuity" category, while the lowest score is in the "Novelty" category. The benchmark value of the Gojek application indicates that the Gojek application has a rating scale that is on the scale of "above average" and "good". Suggestions that can be taken from the results of research that the Gojek application in general has been very good in providing experience for its users, things that need to be improved is in terms of the renewal of the application.